2019
DOI: 10.54607/hcmue.js.16.8.2380(2019)
|View full text |Cite
|
Sign up to set email alerts
|

Listening Comprehension Strategy Instruction: A Review of Previous Studies

Abstract: Bài báo nhằm mục đích tổng hợp những nghiên cứu có giá trị về hiệu quả của việc hướng dẫn các chiến lược nghe đối với khả năng nghe hiểu và cách thức sử dụng các chiến lược này của người học. Bài báo tập trung phân tích những nghiên cứu liên quan đến các loại chiến lược nghe của người học và sự khác biệt của họ sau quá trình nghiên cứu. Những nghiên cứu được nhắc đến trong báo cáo này đã được thực hiện ở Việt Nam và trên thế giới. Dựa trên so sánh, đối chiếu các nghiên cứu, bài báo đưa ra một số kết luận sư ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The student gains input into the language through listening (Rost, 1994). Despite this, in Vietnam where the testing system has paid more attention to grammar and vocabulary, the listening skill has received less attention from instructors and high school students (Ngo, 2019). This somehow has created some difficulties for high school graduates when entering university where they are required to learn English for communication purposes, including listening comprehension.…”
Section: Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The student gains input into the language through listening (Rost, 1994). Despite this, in Vietnam where the testing system has paid more attention to grammar and vocabulary, the listening skill has received less attention from instructors and high school students (Ngo, 2019). This somehow has created some difficulties for high school graduates when entering university where they are required to learn English for communication purposes, including listening comprehension.…”
Section: Background To the Studymentioning
confidence: 99%
“…The researchers have searched the related literature and found that the metacognitive approach might be a solution to these problems. Research in international and Vietnamese contexts shows the positive effects of metacognitive listening strategies (Vandergrift, 2012) on the listening comprehension of EFL learners and on their awareness of metacognitive activities (Abdullah, 2010;Bozorgian, 2012;Movahed, 2014, Vandergrift & Tafaghodtari, 2010Le, 2006;Ngo, 2015;Ngo, 2019). However, most of the related studies have focused on finding out which strategies in the approach worked in which circumstances.…”
Section: The Researchers Used Metacognitive Awarenessmentioning
confidence: 99%